2011
DOI: 10.3109/00365521.2011.584897
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of disease activity in IBD at the time of diagnosis by the use of clinical, biochemical, and fecal markers

Abstract: In UC, both biochemical and fecal markers are related to disease activity and extent of disease, whereas in CD, the fecal calprotectin concentration is a reliable marker of mucosal affection, but not for systemic disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
64
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 31 publications
11
64
0
Order By: Relevance
“…Presumably, FC levels increase rapid ly both in proctosigmoiditis and extensive coli tis, because the main sources of this protein are granulocytes and lymphocytes, which massive ly infiltrate the bowel wall during ac tive inflam mation. These findings partially confirm the re sults of Ricanek et al, 10 who reported no differ ence in FC levels between left sided UC and pan colitis, while showing them to be significantly lower in proctitis.…”
supporting
confidence: 90%
“…Presumably, FC levels increase rapid ly both in proctosigmoiditis and extensive coli tis, because the main sources of this protein are granulocytes and lymphocytes, which massive ly infiltrate the bowel wall during ac tive inflam mation. These findings partially confirm the re sults of Ricanek et al, 10 who reported no differ ence in FC levels between left sided UC and pan colitis, while showing them to be significantly lower in proctitis.…”
supporting
confidence: 90%
“…Recently, there has been increasing evidence that the level of fecal calprotectin (FCAL) is very sensitive and specifi c for the presence of intestinal infl ammation in both CD and UC ( 16,17 ). FCAL is released from the breakdown of neutrophils in the intestines, and is not elevated in the absence of gut infl ammation.…”
Section: Introductionmentioning
confidence: 99%
“…In ulcerative colitis, FC has been shown to be lower in proctitis compared to those with extensive and left-sided disease. Ricanek et al [57] showed than median FC concentration was higher in patients with extensive and left sided disease distribution compared with proctitis (740 vs. 86 μg/g, p < 0.001). The cutoff for active proctitis is therefore likely to be lower than that for left-sided and pan colitis but more studies are needed.…”
Section: Fecal Biomarkers Ibd: Special Situationsmentioning
confidence: 99%